Site‐Specific Isotope‐Labeling of Inosine Phosphoramidites and NMR Analysis of an Inosine‐Containing RNA Duplex. Issue 43 (8th September 2016) - Dallmann, Andre; Beribisky, Alexander V.; Gnerlich, Felix; Rübbelke, Martin; Schiesser, Stefan; Carell, Thomas; Sattler, Michael
Abstract: Structural features and internal dynamics of inosine‐containing RNAs are poorly understood. NMR studies of such RNAs require 13 C, 15 N‐labeling, which cannot be achieved using in vitro transcription as inosine and guanosine are not distinguished by RNA polymerase. Herein, we report the synthesis of an inosine phosphoramidite with selective 13 C8 and 15 N7‐isotope incorporation in the base and uniform 13 C‐labeling of the ribose. Chemical synthesis of an RNA duplex containing four consecutive IU base pairs with this optimized isotope‐labeling scheme greatly simplifies NMR spectra and resolves signal overlap. The absence of detectable NMR signals of imino protons and unusual inter‐residue NOE correlations in this RNA indicate deviations from standard A‐form geometry, consistent with reduced stability of this duplex seen in UV melting studies compared to its nonedited RNA counterparts. These studies indicate that the introduction of IU base pairs distorts and destabilizes RNA helices significantly compared to the also noncanonical GU base‐pairs. Our optimized isotope‐labeling scheme enables high‐resolution NMR studies of inosine‐edited RNAs. Abstract : Off down the strand : A novel site‐specific isotope‐labeling strategy is demonstrated for an inosine‐edited RNA. NMR analysis of an RNA duplex with four IU mismatches utilizing this approach reveals deviations from canonical RNA helix conformation and reduced thermodynamic stabilities compared to nonedited RNA constructs (see figure).